MOBILE TECHNOLOGY AND THE CREATION OF AN ARTIFICIAL ENGLISH-LANGUAGE ENVIRONMENT OUTSIDE THE CHINESE CLASSROOM - Abonales, Therese Padilla (PEOPLE: International Journal of Social Sciences, 2016)
Despite the growing number of rich people in China and the ever-increasing exposure of the Chinese to the West, especially to English-speaking cultures, English proficiency is still elusive. One of the obvious reasons for this is the lack of a natural environment for speaking the language. In China, the official language is Mandarin with a number of dialects and/or different Chinese languages as first language. This paper proposes an artificial English-language environment wherein students learning English as a Foreign Language or English as a Second Language can enjoy using English to an extent that it actually becomes a fun habit for them to speak it. This is possible with the use of mobile technology, something which the young (and even the not-so-young) cannot seem to live without. In any given university classroom, 100% of the students use smartphones with an active internet connection. The English teacher can maximize the functionality of this device in creating an artificial English-language environment for the students, not only inside but outside the classroom as well.